Modernization of local history training for future geography teachers (Pedagogy of Higher and Secondary Education, 2012)
Bondarenko O. V. Modernization of local history training for future geography teachers.The article deals with the problem of modernization of country study training of students geographers of pedagogical higher educational establishments. The author considers the methodology of forming of future geography teachers’ readiness for country study work with pupils.
Keywords: country study work; readiness for country study work; modernization; methodology of forming of readiness for country study work.